2017
DOI: 10.1039/c7nr04842d
|View full text |Cite
|
Sign up to set email alerts
|

Biotemplated synthesis of magnetic filaments

Abstract: With the aim of creating one-dimensional magnetic nanostructures, we genetically engineered flagellar filaments produced by Salmonella bacteria to display iron- or magnetite-binding sites, and used the mutant filaments as templates for both nucleation and attachment of the magnetic iron oxide magnetite. Although nucleation from solution and attachment of nanoparticles to a pre-existing surface are two different processes, non-classical crystal nucleation pathways have been increasingly recognized in biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…49 Linear, filament-like assemblies of ferromagnetic nanoparticles have been made using biological agents and bio-templates. 50,51 Magnetic nanochains have been made by causing chain-like assembly applying external magnetic fields on super-paramagnetic nanoparticle clusters, fixed by an additional layer of silica. 52 In summary, one can divide available MF systems in two classes: those containing magnetisable (or super-paramagnetic) particles and those made of ferromagnetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…49 Linear, filament-like assemblies of ferromagnetic nanoparticles have been made using biological agents and bio-templates. 50,51 Magnetic nanochains have been made by causing chain-like assembly applying external magnetic fields on super-paramagnetic nanoparticle clusters, fixed by an additional layer of silica. 52 In summary, one can divide available MF systems in two classes: those containing magnetisable (or super-paramagnetic) particles and those made of ferromagnetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of Bereczk-Tompa et al . 43 and being the iron binding by negatively charged amino acids (in extended surfaces) a less specific process than the binding of previously formed nuclei, magnetite nucleation induced by the ionotropic effect is probably kinetically favoured in the case of MamC 44 . HRTEM images of MamC-mediated magnetite crystals in Lopez-Moreno et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that binding proteins, enzymes, or reporter proteins can be inserted into the variable central portion of the flagellin protein, resulting in a plethora of building blocks applicable for functionalized nanotube formation. Flagellin-based fusion proteins with catalytic and molecular recognition functionalities can be assembled to form mixed or block copolymers in a rationally designed manner, opening new horizons for applications in medical diagnostics, environmental monitoring, or bionanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Its terminal regions are highly conserved and required for filament formation, in contrast to the variable middle portion that forms the D3 domain exposed on the surface of the filaments. The D3 domain can be modified or replaced by heterologous segments, enabling the introduction of specific functionalities into the host molecule. These flagellin variants reengineered in the D3 region typically retain their polymerization ability and can be used to make functionalized protein nanotubes in vitro . They can be readily produced by bacteria because they form filaments on the cell surface, which can be removed and purified easily.…”
Section: Introductionmentioning
confidence: 99%